VNG ULMER AU SERVICE ORL DE L'HOPITAL MILITAIRE DE RABAT : PROTOCOLE ET INTERPRETATION - Zaineb KETTANI (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
The assessment of vestibular pathology is a challenge for clinicians. The etiologies of vertigo are varied, and may be benign or, on the contrary, reveal a serious central pathology. This justifies the need to carry out a complete clinical and paraclinical exploration in front of evocative symptoms. Since the 1990s, videonystagmography(VNG) has been designed to record in real time eye movements caused by different stimuli. The development of this device and its clinical applications are the result of the work of a great French otologist, Dr.Erik Ulmer. The VNG has become an essential tool in vestibular exploration which studies the behavior of the vestibule over a range of frequencies between 0.003 and 100Hz through a panoply of tests, to know oculomotricity tests, nystagmus search, kinetic tests and bithermal caloric tests. It allows us to search for a unilateral or bilateral vestibular deficit, to highlight signs of centrality, or to estimate the recovery of a vestibular deficit after rehabilitation. The objective of our work is to provide clinicians interested in vertigo with an easy-to-read manual in order to master the practice and interpretation of the Ulmer VNG, which has been practiced at the ENT department of the Mohammed 5 military training hospital (HMIMV-Rabat) for the last ten years. The Ulmer VNG remains a non-traumatic exploration for patients and the duration of its realization in practice does not exceed 45 minutes, it allows to orientate towards the central or peripheral origin of the disorder by ruling out several etiologies and by avoiding a number of costly complementary examinations for patients that could delay their treatment.
Keywords: Vidéonystagmographie Ulmer; VNG Ulmer; Nystagmus dorigine périphérique; Nystagmus dorigine centrale